Synergistic interaction between lead and cadmium via metal-transporter gene upregulation in mice - Tingting Zhang; Weiqin Xing; James A. Ippolito; Shuangshuang Shao; Xinjun Huang; Yongqiang Yang; Linlin Zhao; Yongxia Cheng; Liping Li (BioMetals, 2026)
This study investigated the potential synergistic interactions between Pb and Cd, and assessed the contribution of transporter gene expression to the synergism. Mice were administered varying doses of Pb (15, 30 and 108 mg kg −1 ) or Cd (1, 2 and 3 mg kg −1 ), or a combination of both in the feed. Liver, kidney and bone samples were analyzed for Cd, Pb, Cu, Mn, Zn and Fe concentrations. For treatments exhibiting synergistic effects, the relative expression levels of the divalent metal transporter 1 ( Dmt1 ), ZRT-IRE-like protein 8 ( Zip8 ) and Zip14 were quantified in the liver and kidney using Quantitative Real-Time Reverse Transcription Polymerase Chain Reaction (qRT-PCR). At 108 mg kg −1 Pb , increasing Cd doses from 0 to 1 mg kg −1 significantly increased Pb concentrations in the kidney, liver and bone by 10.6, 60.2 and 19.6%, respectively; concurrently, the relative expression of the Zip8 in the kidney increased by 69.5%, while Dmt1 and Zip14 expression in the liver increased by 79.0 and 85.6%, respectively. At Cd doses ≥ 1 mg kg −1 , increasing Pb rate resulted in elevated Cd concentrations in the kidney, liver and bone; however, no significant changes in transporter expression levels were observed in the kidney under these treatments, possibly due to the upregulation of transporter genes in the intestines. Results demonstrate that interactions between Pb and Cd can be synergistic, and upregulation of certain transporter genes were responsible for such synergism. These findings offer important insights for mitigating the health risks associated with heavy metal exposure in animal and humans.